2002
DOI: 10.1590/s1415-47572002000400001
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase Mu (GSTM1) null genotype in relation to gender, age and smoking status in a healthy Brazilian population

Abstract: The glutathione S-transferase mu (GSTM1) gene which acts during phase II of xenobiotic metabolism is polymorphic in the population, being absent in about 30-50% of individuals depending on the ethnic group from which they come. Epidemiological studies suggest that individuals who are homozygous null at the GSTM1 locus may have an increased risk of developing various types of neoplastic disease. We used the polymerase chain reaction (PCR) to estimate the frequency of GSTM1 in 176 healthy individuals from the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The correlation between the GSTM1 null genotype and gastric cancer appeared to be more consistent [22,25,27,28,30,53] . On the other hand, other authors failed to demonstrate any statistically significant difference in the GSTM1 polymorphism distribution of gastric cancer patients and controls [24,26,32,36,52,55,56] . Several case-control studies also failed to find a significant association between the CYP2E1/PstI polymorphism and gastric cancer [23,24,26,34] .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The correlation between the GSTM1 null genotype and gastric cancer appeared to be more consistent [22,25,27,28,30,53] . On the other hand, other authors failed to demonstrate any statistically significant difference in the GSTM1 polymorphism distribution of gastric cancer patients and controls [24,26,32,36,52,55,56] . Several case-control studies also failed to find a significant association between the CYP2E1/PstI polymorphism and gastric cancer [23,24,26,34] .…”
Section: Discussionmentioning
confidence: 94%
“…Although studies of the GSTT1 and GSTM1 polymorphisms were performed previously, their association with gastric cancer susceptibility has not been established. Most of them showed no association between the GSTT1 null genotype and risk for gastric cancer [25,32,36,52,53] . However, two others suggested that the GSTT1 null genotype might confer an increased risk for gastric cancer [39,54] .…”
Section: Discussionmentioning
confidence: 99%
“…This has been evidenced by the recent meta-analysis of Benhamou et al [10] who showed the GSTM1 deletion carries only a small risk of lung cancer. Second, the majority of studies compared complete absence of GSTM1 with carriers of one or two copies of the gene that can be analysed by straightforward genotyping techniques [27,28]. It is, however, possible to determine the number of GSTM1 and GSTT1 alleles [29,30] and there is evidence that GSTT1 allele number is an important modifier of cancer risk as opposed to a simplified comparison between absence and presence of this gene [30].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies involving genes of xenobiotic metabolism have been performed in order to describe the frequency of the mutant alleles and genotypes in different healthy populations ( Garte et al , 2001 ; Gaspar et al , 2002 ; Menoyo et al , 2006 ). Some studies carried out in the Brazilian population described mutant allele and genotype frequencies in several regions ( Arruda et al , 1998 ; Gattás and Soares Viera, 2000; Gaspar et al , 2002 ; Losi-Guembarovski et al , 2002 ; Rossini et al , 2002 ; Amorim et al , 2004 ; Gattás et al , 2004; Hatagima et al , 2004 ; Kvitko et al , 2006 ; Rossini et al , 2006 ).…”
mentioning
confidence: 99%